2007
DOI: 10.1590/s0101-81752007000200019
|View full text |Cite
|
Sign up to set email alerts
|

Análise das atividades biológicas dos venenos de Philodryas olfersii (Lichtenstein) e P. patagoniensis (Girard) (Serpentes, Colubridae)

Abstract: Philodryas olfersii (Lichtenstein, 1823) e P.patagonienis (Girard, 1857) são serpentes colubrídeas da série opistóglifa, restritas à América do Sul. Vários acidentes ocasionados por estas serpentes têm sido relatados, caracterizando-se por ação local importante: dor, edema e hemorragia. É um acidente muito semelhante àquele causado por serpentes do gênero Bothrops Wagler, 1824 e muitas vezes os pacientes são tratados com soro antibotrópico. Poucos estudos tratam da caracterização destes venenos, assim tivemos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 49 publications
3
16
0
5
Order By: Relevance
“…Furthermore, there is at least one report of death caused by a rear-fanged snake, Philodryas olfersii in southern Brazil (3). As a result, the biological activity and biochemical characterization of venom from these animals has received more attention in this decade (4)(5)(6)(7). However, unlike venomous snakes, secretion from the venom gland of rear-fanged snakes is difficult to obtain in suitable quantities, so some species have started being kept in captivity at Butantan Institute Herpetology Laboratory (LHIB) with the aim of producing venom from periodical extractions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is at least one report of death caused by a rear-fanged snake, Philodryas olfersii in southern Brazil (3). As a result, the biological activity and biochemical characterization of venom from these animals has received more attention in this decade (4)(5)(6)(7). However, unlike venomous snakes, secretion from the venom gland of rear-fanged snakes is difficult to obtain in suitable quantities, so some species have started being kept in captivity at Butantan Institute Herpetology Laboratory (LHIB) with the aim of producing venom from periodical extractions.…”
Section: Introductionmentioning
confidence: 99%
“…Potent SVMPs are observed in the venoms of snakes from the genus Philodryas (Assakura et al, 1994;Rocha et al, 2006;Sánchez et al, 2014), and venoms from these species in particular have been commonly reported to induced hemorrhage, myonecrosis and edema (Peichoto et al, 2005;Nery et al, 2014;Sánchez et al, 2014;Oliveira et al, 2017). The proteolytic activity of Philodryas venoms is inhibited by metal chelators (Assakura et al, 1992;Acosta et al, 2003;Peichoto et al, 2005Peichoto et al, , 2012Rocha and Furtado, 2007), suggesting that SVMPs are resulting in these clinical snakebite symptomologies; in some species, serine proteinases may also be involved (Assakura et al, 1994;Peichoto et al, 2005;Ching et al, 2006). In comparison to venom from the pit viper species FIGURE 2 | Reduced SDS-PAGE protein profiles for various rear-fanged snake venoms.…”
Section: Metalloproteinasesmentioning
confidence: 99%
“…The minimum dose was defined as the lowest venom dose required for the formation of 30% paw oedema (Rocha and Furtado, 2007) and was evaluated after subplantar injection of venom, in the right footpad of mice. For inhibition studies, a fixed amount of Bothrops atrox venom (0, 20 mg/25 µL PBS) was mixed with Brosimum guinanensis extract concentrations different (1, 25; 2,5; 5,0; 7,5 and 10 mg de BGE/Kg/25 µL PBS).…”
Section: Oedema Inductionmentioning
confidence: 99%